Design and Development of Ankle-Foot Rehabilitation Exerciser (AFRE) System Using Pneumatic Actuator - Osman, Khairuddin; Mohd Faudzi, Ahmad 'Athif; Rahmat, M.F.; Kai, Chai Chang; Suzumori, Koichi (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This research presents the design and development of a novel strategy for an Ankle-Foot Rehabilitation Exerciser (AFRE) system. AFRE system can be used Continuous Passive Motion (CPM) device and strength endurance training device for early stage functional rehabilitation. The designed mechanism can allow desired maximum and minimum Range of Motion (ROM) for dorsiflexion and plantar flexion (upwards and downwards stretching). This device consists of a new moveable mechanism design prototype using a new double acting Intelligent Pneumatic Actuator (IPA), embedded controller and communication protocol. The drive system consists of a nonlinear moving pneumatic actuator that controls the angle position, force and compliance for stiffness characteristic of the ankle-foot orthosis platform. In addition, the device can be configured through MATLAB via personal computer where the user can adjust the required ROM and resistance for the user in real-time. Analysis carried out during the system validation and testing through selected subjects are presented and discussed. This AFRE system is expected to substitute the traditional therapy and motorized rehabilitation device to increase the healing time of the patient specifically.